Swiss residents' arguments for and against a career in medicine - Klaghofer Richard; Dietz Claudia; Buddeberg-Fischer Barbara; Buddeberg Claus (BMC, 2006)
Abstract Background In some Western countries, the medical profession is continuously losing prestige, doctors are claiming of high demands, low rewards, and difficult structural working conditions. This study aimed to investigate the arguments given by Swiss residents for and against a career in medicine. Methods As part of a prospective cohort study of Swiss medical school graduates on career development, 567 fourth-year residents were asked to answer the free-response item of what arguments there still were in favour of or against a career in medicine. They also indicated whether they would choose the medical profession all over again (yes/no). The statements were transcribed, content categories inductively formulated, and their descriptions written down in a code manual. Arguments were encoded according to the code manual and assigned to eight content categories (Mayring's content analysis). Frequency distributions were given for categories and tested with Chi2-tests for differences in gender, speciality fields, and whether or not the respondent would again choose a career in medicine. Results The 567 participants made 1,640 statements in favour of and 1,703 statements against a career in medicine. The content analysis of the residents' answers yielded eight categories with arguments both for and against a career in medicine. Of all "statements for" responses, 70% fell into the two top-ranking categories of Personal experiences in day-to-day working life (41.2%) and Interpersonal experiences in professional relationships (28.8%). The top-ranking category of the "statements against" arguments was General work-related structural conditions (32%), followed by Social prestige and health-policy aspects (21%). Main arguments in favour of a career in medicine were interdisciplinary challenge, combination of basic sciences and interpersonal concerns, helping suffering people, guarantee of a secure job; arguments against comprised high workload, time pressure, emotional stress, poorly structured continuing education, increasing bureaucracy, work-life imbalance, low income, and decreasing social prestige. The statements revealed few differences depending on gender, medical field, and attitude towards choosing the medical profession again; one out of five young doctors would not do so. Conclusion Residents' chief complaint is deteriorating structural working conditions, including unfavourable work-life balance. Making medicine an attractive profession again will require sustainable changes in health-policy framework and social reward.